Fatty Acid Composition, Steroid Content, In Vitro Antioxidant and Antidiabetic Potentials of Citrullus lanatus and Carica papaya Seed Oils - Bamidele Martin Amos-Tautua; Imomotimi Timipa Ajoko; Rafiu Oladiran Raji (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Plant-derived oils rich in bioactive constituents have attracted attention as potential antioxidant and antidiabetic agents. The present study assessed the phytochemical profile, antioxidant activity, enzyme inhibitory activity, and fatty acid profile of pawpaw (Carica papaya) and watermelon (Citrullus lanatus) seed oils. Antioxidant activity was assessed by DPPH radical scavenging and FRAP assays, while antidiabetic activity was evaluated through in vitro alpha-amylase and alpha-glucosidase inhibition. Phytochemical analysis revealed triterpenoids, steroids, and cardiac glycosides in both oils. In the DPPH assay, pawpaw and watermelon seed oils showed maximum inhibitions of 13.32% and 15.91% at 200 µg/mL, respectively; while the FRAP values were low (9.06 and 14.51 µM Fe2+/mg). Enzyme inhibition assays indicated differential activity: pawpaw seed oil strongly inhibited alpha-glucosidase (84.69% at 1000 µg/mL) while watermelon seed oil strongly inhibited alpha-amylase (81.81%). GC-MS analysis of the oils revealed the most abundant fatty acids as cis-10-heptadecenoic acid (895.57 mg/L) arachidonic acid (263.49 mg/L), 5,8,11,14,17-eicosapentaenoic acid (241.80 mg/L). Essential fatty acids such as gamma-linolenic acid and docosahexaenoic acid (DHA) were also present. In conclusion, the seed oils exhibit moderate antioxidant activity and complementary enzyme inhibitory effects. Their rich unsaturated fatty acid profiles support potential use as functional dietary oils for diabetes management.